Journalism and digital labor : experiences of online news production - Neilson, Tai (New York, NY : Routledge, 2021)
"This book investigates journalists' work practices, professional ideologies, and the power relations that impact their work, arguing that reporters' lives and livelihoods are shaped by digital technologies and new modes of capital accumulation. Tai Nelson weaves together ethnographic approaches and critical theories of digital labor. Journalists' experiences are at the heart of the book, which is based on interviews with news workers from Aotearoa New Zealand and the United States. The book also adopts a critical approach to the political economy of news across global and local contexts, digital start-ups, legacy media, nonprofits, and public service organizations. Each chapter features key debates illustrated by journalists' personal narratives. This book will be of great interest to researchers and students of journalism, media and communication, cultural studies, and the sociology of work"--
Introduction: The digital reporter -- Global changes and national news -- The digitization of journalism -- The entrepreneurial journalist and subjectivities of digital labor -- Social media metrics and the reified journalist -- The news machine -- Unionizing digital newsrooms -- Conclusion: Writing for algorithms -- Afterword: The ideology problem.
OCLC-licensed vendor bibliographic record.
Keywords: Online journalism -- Labor productivity; Journalists -- Effect of technological innovations on; Journalists -- Job stress; Journalists -- Labor unions -- Organizing; Online journalism -- Objectivity; SOCIAL SCIENCE / Media Studies